DYNAMISM OF BUGIS COMMUNITY IN BADUNG REGENCY AND DENPASAR CITY - Suwitha, I Putu Gede (E-Journal of Cultural Studies; Volume 7, Number 2, May 2014, 2014)
The Bugis community in Badung Regency and Denpasar City had played political and economic roles for a long time. Historically, its existence had never been disputed as it had a political entity as its patron. In addition, cultural exchange in many social, political and economic activities also contributed to this, causing the relationship among ethnic groups became collaborative rather than competitive. This present study was conducted using qualitative and descriptive method. The data were collected through in- depth interview. What the informants knew about the Bugis community was collected using this technique. The information which needed to be deepened was continued using interpretative and practical approaches.   The result of the present study showed that the Bugis community had played political and economic roles for a long time. It also showed that it was contributive to the Balinese community. They made adjustment and adaptation economically and culturally. It formed an identity which was not given but was adjusted to what was needed. They established public spaces where they could establish multicultural life and blew up the local values of the Balinese culture. Now the Bugis people became marginalized (subaltern). As subaltern, they were not able to express themselves. The factors which caused them not to be able to express themselves were their inability to follow the economic change as they were too weak to compete and their inability to compete in tourism in Bali.
Keywords: identity, subaltern, marginalization, multiculturalism.